Stereomicroscopic on-site evaluation in endoscopic ultrasound-guided tissue acquisition of upper gastrointestinal subepithelial lesions - Seigo Nakatani; Kosuke Okuwaki; Masafumi Watanabe; Hiroshi Imaizumi; Tomohisa Iwai; Takaaki Matsumoto; Rikiya Hasegawa; Hironori Masutani; Takahiro Kurosu; Akihiro Tamaki; Junro Ishizaki; Ayana Ishizaki; et al. (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims In stereomicroscopic sample isolation processing, the cutoff value (≥4 mm) of stereomicroscopically visible white cores indicates high diagnostic sensitivity. We aimed to evaluate endoscopic ultrasound-guided tissue acquisition (EUS-TA) using a simplified stereomicroscopic on-site evaluation of upper gastrointestinal subepithelial lesions (SELs). Methods In this multicenter prospective trial, we performed EUS-TA using a 22-gauge Franseen needle in 34 participants with SELs derived from the upper gastrointestinal muscularis propria, requiring pathological diagnosis. The presence of stereomicroscopically visible white core (SVWC) in each specimen was assessed using stereomicroscopic on-site evaluation. The primary outcome was EUS-TA's diagnostic sensitivity with stereomicroscopic on-site evaluation based on the SVWC cutoff value (≥4 mm) for malignant upper gastrointestinal SELs. Results The total number of punctures was 68; 61 specimens (89.7%) contained stereomicroscopically visible white cores ≥4 mm in size. The final diagnoses were gastrointestinal stromal tumor, leiomyoma, and schwannoma in 76.5%, 14.7%, and 8.8% of the cases, respectively. The sensitivity of EUS-TA with stereomicroscopic on-site evaluation based on the SVWC cutoff value for malignant SELs was 100%. The per-lesion accuracy of histological diagnosis reached the highest level (100%) at the second puncture. Conclusions Stereomicroscopic on-site evaluation showed high diagnostic sensitivity and could be a new method for diagnosing upper gastrointestinal SELs using EUS-TA.